2022
DOI: 10.3390/microorganisms10010134
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Microbiomes of the Respiratory Tract and Joints of Feedlot Cattle Mortalities

Abstract: A comparative study of microbiota of the respiratory tract and joints of bovine respiratory disease (BRD) cattle mortalities was undertaken. Nasopharynx, trachea, lung and joint samples were collected from 32 cattle that died of BRD, “cases”, and 8 that died of other causes, “controls”. Bacterial diversity was lower (p < 0.05) in the nasopharynx, trachea and lungs of cases as compared to controls. In cases, alpha-diversity (p < 0.05) was lower in the lungs and joints than the nasopharynx. Proteobacteria,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
2
3
0
Order By: Relevance
“…were more prevalent among lung tissues (38%) than nasal swabs (35%). This result is in complete agreement with those reported in previous studies conducted in Europe (60 and 24.4%, respectively) [ 54 ] and Canada (36 and 8.8%, respectively) [ 68 ], but it was in contrast with previous studies conducted in Europe, where Mycoplasma spp. were more prevalent among nasal swabs than lung tissues [ 69 ].…”
Section: Discussionsupporting
confidence: 93%
“…were more prevalent among lung tissues (38%) than nasal swabs (35%). This result is in complete agreement with those reported in previous studies conducted in Europe (60 and 24.4%, respectively) [ 54 ] and Canada (36 and 8.8%, respectively) [ 68 ], but it was in contrast with previous studies conducted in Europe, where Mycoplasma spp. were more prevalent among nasal swabs than lung tissues [ 69 ].…”
Section: Discussionsupporting
confidence: 93%
“…These data indicate that the bacterial profiles of the lung lavage samples are significantly different in taxa diversity when compared to the nasal and tonsil samples. While lower alpha diversity is typically associated with disease, previous research has reported a similar lower diversity of the lung compared to other respiratory tract locations of post-weaned beef calves (Nicola et al, 2017) and feedlot cattle (McMullen et al, 2020a;Li et al, 2022). This suggests that the lower diversity of the lung lavage samples, as reported in the data presented herein, is not associated with disease.…”
Section: Alpha and Beta Diversitiessupporting
confidence: 71%
“…Many studies report slightly different results for observed sequence variants, including observed operational taxonomic units (OTUs) (Holman et al, 2015), species (Zeineldin et al, 2017;McMullen et al, 2019), amplicon sequence variants (ASVs), and the number of reads (Lima et al, 2016), which can make comparisons among studies difficult. Furthermore, previous results have varied regarding differentially abundant and significantly enriched bacterial taxa as well (Lima et al, 2016;Zeineldin et al, 2017;McMullen et al, 2020;Zeineldin et al, 2020;Raabis et al, 2021;Centeno-Martinez et al, 2022;Li et al, 2022).…”
Section: Introductionmentioning
confidence: 99%